Efficacy and safety profile of SGLT2 inhibitors in patients with type 2 diabetes and chronic kidney disease. Issue 3 (3rd March 2020) - Scheen, André J
ABSTRACT: Introduction : Sodium-glucose cotransporter type 2 inhibitors (SGLT2is) have a complex relationship with the kidney so that their use in patients with type 2 diabetes (T2DM) and diabetic kidney disease (DKD) has long been challenged. Areas covered : SGLT2is in patients with DKD are discussed: renal mechanisms of action, PK/PD characteristics, clinical use in patients with stage 3 DKD, effects on estimated glomerular filtration rate (eGFR) and albuminuria, cardiovascular, and renal outcomes according to renal function, overall and renal safety, SGLT2is new place in updated guidelines. Expert opinion : Whereas initial concerns (reduced glucose-lowering efficacy, early reduction in eGFR) led to restrictions in the use of SGLT2is in patients with DKD, recent positive observations have completely reversed the scene. Indeed, albuminuria is reduced and eGFR is preserved in the long term by SGLT2is. A significant reduction in cardiovascular events and hard renal outcomes was reported even in patients with eGFR 30–60 mL/min/1.73 m 2 . The overall safety profile of SGLT2is is not altered in patients with mild to moderate DKD, with a reduced (rather than increased) risk of acute renal injury. This positive benefit/risk balance led recent guidelines to recommend SGLT2is in patients with T2DM and mild to moderate DKD, especially if albuminuria.